Alleviation of cadmium toxicity and growth enhancement of helianthusannuus and triticum aestivum seedlings through bacterial inoculation - Hasnain, Shahida; Akhtar, Nasreen; Nasim Sabri, Anjum (Universiti Putra Malaysia Press, 1996)
Two Cd-resistant bacterial growth strains MA-9 (Aeromonas) and MA19 (affinities uncertain), which were isolated from ICI effluents, were used to inoculate seeds ifTriticum aestivum (wheat) and Helianthus annuus (sunflower). Both inoculated and non-inoculated seeds were germinated and grown under different concentrations (0, 1, 2 and 3 mM) of CdCl2 for 10 days. Under Cd-stress conditions, bacteria-inoculated plants had better germination and growth than non-inoculated treatments. Bacterial growth enhancement if seedlings was associated with reduced Cd uptake.